2018
DOI: 10.3390/cryst8070275
|View full text |Cite
|
Sign up to set email alerts
|

Quasicrystalline Ordering in Thin Liquid Crystal Films

Abstract: Quasicrystalline ordering was first observed in synthetic multi-component metallic alloys. These solid state materials exhibit quasicrystalline atomic ordering at nanometer length scales. Softmatter systems are another class of versatile materials that can exhibit quasicrystalline ordering across supra-nanometer (>10 nm) to supra-micrometer (>10 µm) length scales as recently observed in materials like-supramolecular dendritic molecules, ABC star polymers, binary nanoparticle systems and block co-polymers in co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 65 publications
0
4
0
Order By: Relevance
“…showed theoretically how LCs can drive the assembly of platelets to form a 2D quasicrystal. [ 18,19 ] By choosing carefully the geometry of the colloidal particles, Senyuk et al. showed how the LC elastic forces could drive the quasicrystalline assembly of truncated pyramids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…showed theoretically how LCs can drive the assembly of platelets to form a 2D quasicrystal. [ 18,19 ] By choosing carefully the geometry of the colloidal particles, Senyuk et al. showed how the LC elastic forces could drive the quasicrystalline assembly of truncated pyramids.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Using the elastic field created by LCs to drive selfassembly in the microscale, Dontabhaktuni et al showed theoretically how LCs can drive the assembly of platelets to form a 2D quasicrystal. [18,19] By choosing carefully the geometry of the colloidal particles, Senyuk et al showed how the LC elastic forces could drive the quasicrystalline assembly of truncated pyramids. [20] One of the characteristics of quasicrystals is the unique diffraction pattern that matches their intrinsic symmetry.…”
mentioning
confidence: 99%
“…Since then, some known structures have been revisited (4,5), pointing toward a larger scale of QC networks that, so far, remain hidden. Besides intermetallics, quasicrystalline ordering has been detected, but only rarely, in chalcogenides (6,7), mesoscale materials (8), terpolymers (9), liquid crystals (10,11), colloids (12), thin films (13,14), proteins (15), or nanoparticle assemblies (16). QC approximants (ACs) represent crystalline materials compositionally and structurally approaching the atomic self-organization present in QCs but with long-range translational order.…”
Section: Introductionmentioning
confidence: 99%
“…Stable dodecagonal (DD; 12-fold) QCs could be observed in bulk chalcogenides (6,7). A limited number of thermodynamically metastable DDQCs and DDACs have been discovered in complex metallic alloys (18)(19)(20), and a few have been discovered in soft QC systems (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%